2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181827
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility pattern of dermatomycosis in a tertiary care hospital of North India

Abstract: <p class="abstract"><strong>Background:</strong> Dermatomycoses affect the outer layers of the skin, nails and hair without tissue invasion and are often caused by dermatophytic molds, candida &amp; non dermatophytic molds. Although not dangerous, they are important as a public health problem particularly in the immunocompromised. There are limited studies on the efficacy of antifungal agents against dermatophytes in North India.</p><p class="abstract"><strong>Methods:&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“… 11 25 26 Indian studies show this trend, wherein the studies from 2014 to 2016 show T. rubrum as the commonest dermatophyte 13 27 and in the later years it is T. mentagrophytes which is commonest. 3 9 28 29 In this study, T. mentagrophytes complex was the commonest isolate, followed by T. rubrum complex and one Microsporum gypseum . This is in complete sync with other studies from nearby areas.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 11 25 26 Indian studies show this trend, wherein the studies from 2014 to 2016 show T. rubrum as the commonest dermatophyte 13 27 and in the later years it is T. mentagrophytes which is commonest. 3 9 28 29 In this study, T. mentagrophytes complex was the commonest isolate, followed by T. rubrum complex and one Microsporum gypseum . This is in complete sync with other studies from nearby areas.…”
Section: Discussionmentioning
confidence: 64%
“…This is in complete sync with other studies from nearby areas. 3 29 Studies from Iran have also reported T. mentagrophytes as the commonest dermatophyte, 10 30 while studies from Turkey, Vietnam, Tunisia, Brazil, and Canada have reported T. rubrum as the commonest. 14 31 32 33 34 35 T. rubrum still remains the commonest dermatophyte in most regions of the world even though the epidemiology is changing in some parts including ours.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 But dissimilar to the study of Sharma et aland Sowmya et al in India. 26,27 30,12,31 Griseofulvin and Fluconazole showed the highest resistance because of universal usage due to their low cost and dosage and their widespread availability in all levels of healthcare centers, which in turn has turned up to increased resistance profile for that drugs. 30 A standardized disc diffusion-based assay for determining the antifungal susceptibility testing of dermatophytes is desirable and has a number of advantages.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, low MIC values with good antifungal susceptibility to itraconazole had been previously reported by Singh et al , Mahajan et al , and Budhiraja et al . [ 4 15 16 ] In a large multicenter study conducted in India, the upper limit wild-type (in μg/mL) against T. mentagrophytes -interdigitale complex based on MIC 95 for terbinafine and griseofulvin were 8 and 64, respectively. High MIC values for terbinafine and griseofulvin were also reported by Shaw et al .…”
Section: Discussionmentioning
confidence: 99%